2014
DOI: 10.1016/j.ijrobp.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Metabolic Tumor Volume and Total Lesion Glycolysis Are Associated With Survival Outcomes in Patients With Locally Advanced Pancreatic Cancer Receiving Stereotactic Body Radiation Therapy

Abstract: Purpose Although previous studies have demonstrated the prognostic value of positron emission tomography (PET) parameters in other malignancies, the role of PET in pancreatic cancer has yet to be well established. We analyzed the prognostic utility of PET for patients with locally advanced pancreatic cancer (LAPC) undergoing fractionated stereotactic body radiation therapy (SBRT). Materials and Methods Thirty-two patients with LAPC in a prospective clinical trial received up to 3 doses of gemcitabine, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…15,16 Given the ability of 18F-FDG PET/CT to identify metastatic disease, there is a potential for quantification of disease burden for prognosis and treatment response by measuring the whole body metabolic tumor volume (MTV) as defined by 18F-FDG uptake, and total lesion glycolysis (TLG), which is the product of the mean standardized uptake value (SUV) and the volume of the tumor. 17,18 Measurement of whole body MTV and TLG has been found to be a potentially valuable prognostic parameter and has been recently utilized to predict the prognosis of various cancers, such as esophageal cancer, 19 multiple myeloma, 20 and small cell lung cancer, 21 and has been utilized to predict treatment response in pancreatic cancer 22,23 and non-small cell lung cancer. 24 Furthermore, automated and semiautomated methods with various thresholds based on the percentage of the SUV max have been developed to decrease inter-and intraobserver variation in tumor volume delineation, which allows data to be more accurate and generalizable.…”
mentioning
confidence: 99%
“…15,16 Given the ability of 18F-FDG PET/CT to identify metastatic disease, there is a potential for quantification of disease burden for prognosis and treatment response by measuring the whole body metabolic tumor volume (MTV) as defined by 18F-FDG uptake, and total lesion glycolysis (TLG), which is the product of the mean standardized uptake value (SUV) and the volume of the tumor. 17,18 Measurement of whole body MTV and TLG has been found to be a potentially valuable prognostic parameter and has been recently utilized to predict the prognosis of various cancers, such as esophageal cancer, 19 multiple myeloma, 20 and small cell lung cancer, 21 and has been utilized to predict treatment response in pancreatic cancer 22,23 and non-small cell lung cancer. 24 Furthermore, automated and semiautomated methods with various thresholds based on the percentage of the SUV max have been developed to decrease inter-and intraobserver variation in tumor volume delineation, which allows data to be more accurate and generalizable.…”
mentioning
confidence: 99%
“…However, the current study showed the prognostic roles of OS and RFS in MTV only in univariate analysis. It is well known that pretreatment MTV and TLG are potent prognostic factors in various cancers [29,30,31]. Nevertheless, conflicting results regarding the prognostic role of sequential F-18 FDG PET/CT still exist in LAEC patients treated with preoperative CRT.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] However, conflicting results regarding prognostic role of sequential 18 F-FDG PET/CT still exist in LARC patients treated with preoperative CCRT. Lee et al 30 reported that the TLG of the primary tumor in the initial 18 F-FDG PET/CT can be considered as a prognostic factor for neoadjuvant CCRT in patients with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%